Seaweed Diversity of the Langkawi Islands with emphasis on the Northeastern Region - Siew-Moi, Phang,; Ching-Lee, Wong,; Phaik-Eem, Lim,; Hui-Yin, Yeong,; Cheong-Xin, Chan, (Malaysian Journal of Science, 2005)
The tally of Malaysian marine algae stands at 377 specific and infraspecific taxa (17 Cyanophyta, 102 Chlorophyta, 186 Rhodophyta and 72 Phaeophyta). Eighty-four taxa of seaweeds (1 Cyanophyta, 25 Chlorophyta, 62 Rhodophyta and 14 Phaeophyta) have been identified from the Langkawi Islands. Commonly found taxa include species of Padina (Phaeophyta), Halimeda, Caulerpa, Bryopsis (Chlorophyta), Gracilaria, Acanthophora, Asparagopsis, Polysiphonia, and Hypnea (Rhodophyta). A relatively high diversity of seaweeds is found in the Langkawi Islands. Biomass is low except for some green seaweed like the Caulerpa species, which grow abundantly on the nets of the fish cages in the estuaries. The seaweed flora of Langkawi is quite distinct from that of Peninsular Malaysia and East Malaysia. It may have elements common to the Andaman Sea flora.